Polymorphisms and plasma level of transforming growth factor-Beta 1 and risk for preeclampsia: a systematic review. - Xun Li; Lin Shen; Hongzhuan Tan (PLoS ONE)
Background Transforming growth factor-beta 1 (TGF-β1) is thought to be involved in the pathogenesis of preeclampsia (PE), but the results are inconsistent among studies. This article aims to compile an overview of the studies about the associations of TGF-β 1 polymorphism and plasma level with PE risk and to provide recommendations for future research. Methods and results The databases PubMed, Embase and Web of Science were searched up to December 2013. Five studies investigating the associations of four polymorphisms with the risks of PE were involved. A meta-analysis was conducted for the 869T>C polymorphism and PE risk. The results show that genotype TT of 869T>C polymorphism is a protective factor of PE (pooled odds ratio=0.73, 95% CI: 0.56, 0.95). Eight case-control studies reported the plasma level of TGF-β 1. The substantial heterogeneity among studies may be attributed to the differences in the blood sample processing and the TGF-β 1 analysis kits. The results suggest that plasma TGF-β 1 level in the second trimester was significantly lower in the PE group than in the normal pregnancy group, but was significantly higher in the PE group during the third trimester. Conclusions The current results support that the TGF-β 1 869 T>C polymorphism was associated with the risk of PE. However, the number of eligible studies is small and more studies are needed to clarify whether this association can be detected on larger sample sizes and different populations. Owing to the heterogeneity between studies, no conclusion on the association between plasma TGF-β 1 level and PE risk can be drawn from this review. Further studies about the TGF-β 1 levels at different stages of pregnancy and the development of TGF-β 1 assay methodology are required to reveal the role of TGF-β 1 in the pathological development of PE.